The use of bolus in postmastectomy radiation therapy for breast cancer: A systematic review. (July 2021) - Dahn, Hannah M.; Boersma, Liesbeth J.; de Ruysscher, Dirk; Meattini, Icro; Offersen, Birgitte V.; Pignol, Jean-Philippe; Aristei, Cynthia; Belkacemi, Yazid; Benjamin, Dori; Bese, Nuran; Coles, Charlotte E.; Franco, Pierfrancesco; et al.
Graphical abstract: Highlights: Our systematic review of bolus use during PMRT made two important findings: Bolus use leads to more acute toxicity. Bolus use does not seem to improve local control, unless patient is high risk. Bolus may be only indicated for patients with a high risk of local recurrence. Abstract: Purpose: Post mastectomy radiation therapy (PMRT) reduces locoregional recurrence (LRR) and breast cancer mortality for selected patients. Bolus overcomes the skin-sparing effect of external-beam radiotherapy, ensuring adequate dose to superficial regions at risk of local recurrence (LR). This systematic review summarizes the current evidence regarding the impact of bolus on LR and acute toxicity in the setting of PMRT. Results: 27 studies were included. The use of bolus led to higher rates of acute grade 3 radiation dermatitis (pooled rates of 9.6% with bolus vs. 1.2% without). Pooled crude LR rates from thirteen studies (n = 3756) were similar with (3.5%) and without (3.6%) bolus. Conclusions: Bolus may be indicated in cases with a high risk of LR in the skin, but seems not to be necessary for all patients. Further work is needed to define the role of bolus in PMRT.